Review of After a Fall: A Sociomedical Sojourn by Laurel Richardson - Linda A. Treiber (Journal of Public and Professional Sociology)
This a review of Richardson, Laurel. 2013. After a Fall: A Sociomedical Sojourn. Walnut Creek, CA: Left Coast Press. ISBN: 978-1-61132-317-7, paperback, 268 pages. The book is an example of an autoethnography, detailing Richardson's stay in a nursing home.